Проблеми та концепції ефективного розвитку підприємств аграрного сектору . - Prokopets, Liudmyla; Smola, Maryna; Dolitsoj, Olga (Прокопець Л.В., Смола М.Р, Доліцой О.Ю. Проблеми та концепції ефективного розвитку підприємств аграрного сектору . Науково-виробничий журнал «БІЗНЕС-НАВІГАТОР». 2020. № 2 (58). С. 12-16., 2020)
Аграрний сектор економіки країни – це повноцінний комплекс, пов’язаний з природно географічними умовами, ресурсами, техніко-технологічними можливостями та професійними спеціалістами. Наявні проблеми агропромислового комплексу є сукупністю політичних та соціально-психологічних факторів, що впливають на розвиток аграрного сектору й створюють «вузлові» місця у функціонуванні АПК України. У статті досліджено сучасний стан аграрного сектору та перспективи його розвитку в умовах вітчизняного економічного середовища. Проаналізовано основні результати діяльності суб’єктів господарювання, включаючи низку негативних тенденцій. Обґрунтовано перспективні напрями розвитку для покращення показників ефективності підприємств агропромислового комплексу України, а саме вдосконалення інфраструктури аграрного ринку, підвищення обсягів та ефективності фінансово-кредитного забезпечення сільського господарства
The agrarian sector of the country’s economy is a full-fledged complex connected with natural geographical conditions, resources, technical and technological capacities and professional specialists. The existing problems of the agro-industrial complex are a set of political and socio-psychological factors that influence the development of the agrarian sector and create «nodal» places in the functioning of agriculture of Ukraine. Due to the current crisis in the functioning of the agrarian economy and rural social development, the development of socially-oriented market relations is being hampered. That is why the problem of further improving the level of efficiency of this industry is urgent today. Ukraine has considerable potential for agricultural development and the transformation of the agrarian sector into a key and cost-effective area of the national economy. Favorable climatic conditions for the development of different directions of agriculture, fertile soils and national inclination of the population to work in this field contribute to the development of agro-industrial complex, obtaining high economic and financial indicators, providing products not only domestic but also the external market. All these, as well as other conditions and resources shape the competitive advantages of the development of the agricultural sector of the country’s economy. In the work the current state of the agrarian sector and prospects of its development in the conditions of the domestic economic environment are investigated. We have analyzed the main results of business entities, including a number of negative trends. Prospective directions of development for improvement of indicators of efficiency of the enterprises of agro-industrial complex of Ukraine are substantiated, namely improvement of infrastructure of the agrarian market, increase of volumes and efficiency of financial and credit support of agriculture. The research methods used in the process of writing the article involve the application of general scientific and empirical techniques of economic science, based on a systematic approach. In addition, general research methods such as generalization and comparison were used in the process. The results of the study are to develop proposals to improve the functioning of the agricultural sector of Ukraine
Keywords: інвестиції; агропідприємства; ціноутворення; концепція; рентабельність; експлуатація засобів виробництва; investments; agricultural enterprises; pricing; concept; profitability; operation of production facilities